Yeast mannoproteins are expected to be a novel potential functional food for attenuation of obesity and modulation of gut microbiota - Li, Xiang; Wu, Junsong; Kang, Yijun; Chen, Dan; Chen, Guijie; Zeng, Xiaoxiong; Wang, Jialian (Frontiers in Nutrition, 2022)
The yeast mannoproteins (MPs), a major component of yeast cell walls with large exploration potentiality, attracted an increasing attention due to its beneficial effects. However, the information about the anti-obesogenic activity of MPs is still limited. Thus, the effects of MPs on the high-fat diet (HFD) induced obesity and dysbiosis of gut microbiota were investigated in this work. The result showed that MPs could significantly attenuate the HFD-induced higher body weight, fat accumulation, liver steatosis and damage. Simultaneously, the inflammation in HFD induced mice was also ameliorated by MPs. The pyrosequencing showed MPs intervention could lead to an obvious change in the structure of gut microbiota. Furthermore, the prevention of obesity by MPs is highly linked to the promotion of Parabacteroides distasonis (increased from 0.39±0.12% to 2.10±0.20%) and inhibition of Lactobacillus (decreased from 19.99±3.94% to 2.68±0.77%). Moreover, the increased level of acetate (increased from 3.28±0.22 mmol/g to 7.84±0.96 mmol/g) and activation of G protein-coupled receptors (GPRs) by MPs may also contribute to the prevention of obesity. Thus, our preliminary findings revealed that MPs from yeast could be explored as potential prebiotics to modulate the gut microbiota and prevent the HFD-induced obesity.